Transcriptomic insights into the molecular mechanism of abietic acid promoting growth and branching in Armillaria gallica - Luo, Chun; Song, Yu; Meng, Lina; Cheng, Yajie; Dai, Huiping; Qiao, Yanming; Xie, Xiuchao (Frontiers in Microbiology, 2025)
Armillaria gallica, a valuable edible and medicinal fungus, is essential for the symbiotic cultivation of the traditional Chinese medicinal herb Gastrodia elata. Abietic acid, a plant-derived secondary metabolite, modulates microbial growth and metabolism. This study investigates the effects of abietic acid on A. gallica growth and branching using phenotypic analysis and transcriptomic approaches to uncover underlying molecular mechanisms. The experiment compared an abietic acid treatment group (0.6 g/L) with a control group, assessing growth over several days via biomass measurements, rhizomorph counting, and RNA sequencing for transcriptomic profiling. Abietic acid significantly promoted A. gallica growth and branching, with the most pronounced effects on the third day: dry biomass weight increased by 302% and total rhizomorphs by 378.4% (p < 0.01). Transcriptomic analysis showed upregulation of GH5, GH16, MFS, and NAD(P)-binding protein genes in the treatment group, optimizing carbon utilization, cell wall remodeling, and nutrient transport. These findings elucidate abietic acid’s role in regulating A. gallica development and provide a theoretical foundation for enhancing the symbiotic cultivation of G. elata and A. gallica.